High seed diversity and availability increase rodent community stability under human disturbance and climate variation - Yang, Xifu; Gu, Haifeng; Zhao, Qingjian; Zhu, Yunlong; Teng, Yuwei; Li, Ying; Zhang, Zhibin (Frontiers in Plant Science, 2022)
The relationship between diversity and stability is a focus in community ecology, but the relevant hypotheses have not been rigorously tested at trophic and network levels due to a lack of long-term data of species interactions. Here, by using seed tagging and infrared camera tracking methods, we qualified the seed-rodent interactions, and analyzed the associations of rodent community stability with species diversity, species abundance, and seed-rodent network complexity of 15 patches in a subtropical forest from 2013 to 2021. A total of 47,400 seeds were released, 1,467 rodents were marked, and 110 seed-rodent networks were reconstructed to estimate species richness, species abundance, and seed-rodent network metrics. We found, from younger to older stands, species richness and abundance (biomass) of seeds increased, while those of rodents decreased, leading to a seed-rodent network with higher nestedness, linkage density, and generality in older stands, but higher connectance in younger stands. With the increase of temperature and precipitation, seed abundance (biomass), rodent abundance, and the growth rate of rodent abundance increased significantly. We found rodent community stability (i.e., the inverse of rodent abundance variability) was significantly and positively associated with seed diversity, seed availability, linkage density and generality of seed-rodent networks, providing evidence of supporting the Bottom-Up Diversity‒Stability Hypotheses and the Abundant Food Diversity‒Stability Hypothesis. Our findings highlight the significant role of resource diversity and availability in promoting consumers’ community stability at trophic and network levels, and the necessity of protecting biodiversity for increasing ecosystem stability under human disturbance and climate variation.